Mejoramiento genético y actividades relacionadas. Mejoramiento de características individuales. Calidad nutricional - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
The principal activities carried out in 1986 in the nutrition and quality lab. are reported. A statistical analysis of all the parameters of acceptability on all bean materials evaluated in the lab. from 1981 to 1985 was executed. A joint project was carried out between CIAT and Instituto de Nutricion de Centroamerica y Panama (Costa Rica) on methods to measure cooking time. Studies also aimed at identifying the important parameters for water absorption and at determining the influence of site, planting time, and var. of the cv. on acceptable nutritional characteristics. A joint project with Italy's National Institute of Nutrition was initiated to study tannins, fiber content, and other factors responsible for the low digestibility of beans; likewise, a prototype model of a modified Mattson's automatic cooker was assessed. No significant differences were found for the protein content among the majority of the tested var., but some differences were observed for seed color. Planting time has a marked effect on protein content. Results from planting of Rojo 70 and Rojo de Seda in Palmira, Restrepo, and Quilichao (Colombia) indicate that site is strongly correlated to grain hardness, water absorption, and cooking time. (CIAT)